Speciation with gene flow: Evidence from a complex of alpine butterflies (Coenonympha, Satyridae). Issue 11 (3rd May 2019) - Capblancq, Thibaut; Mavárez, Jesús; Rioux, Delphine; Després, Laurence
Abstract: Until complete reproductive isolation is achieved, the extent of differentiation between two diverging lineages is the result of a dynamic equilibrium between genetic isolation and mixing. This is especially true for hybrid taxa, for which the degree of isolation in regard to their parental species is decisive in their capacity to rise as a new and stable entity. In this work, we explored the past and current patterns of hybridization and divergence within a complex of closely related butterflies in the genus Coenonympha in which two alpine species, C. darwiniana and C. macromma, have been shown to result from hybridization between the also alpine C. gardetta and the lowland C. arcania . By testing alternative scenarios of divergence among species, we show that gene flow has been uninterrupted throughout the speciation process, although leading to different degrees of current genetic isolation between species in contact zones depending on the pair considered. Nonetheless, at broader geographic scale, analyses reveal a clear genetic differentiation between hybrid lineages and their parental species, pointing out to an advanced stage of the hybrid speciation process. Finally, the positive correlation observed between ecological divergence and genetic isolation among these butterflies suggests a potential role for ecological drivers during their speciation processes. Abstract : We explored the past and current patterns of hybridization and divergence within a complex of closely related butterflies in the genus Coenonympha in which two alpine species, C. darwiniana and C. macromma, have been shown to result from hybridization between the also alpine C. gardetta and the lowland C. arcania . By testing alternative scenarios of divergence among species, we show that gene flows have been uninterrupted throughout the speciation process, although leading to different degrees of current genetic isolation between species in contact zones depending on the pair considered.